Does the System of Rice Intensification make a difference to resource use efficiency? evidence from Tripura, India - Saddam H Majumder; P B Gogoi; J P Hazarika; Nivedita Deka (Agricultural Economics Research Review, 2023)
Using data from 120 rice farmers in Tripura, this paper compares resource use efficiency in rice production under the System of Rice Intensification (SRI) vis-à-vis conventional methods. The results show that the SRI uses less seeds and irrigation without adversely affecting rice yield, leading us to conclude that the SRI is more efficient than the conventional method of rice cultivation.